(untitled) (Journal of the College of Basic Education, 2023)
Summary of the research:The study of international relations is one of the studies that has recently witnessed remarkable interest and its importance. Turkish-Azerbaijani cultural relations, specifically language and education, have been studied. The topic has not been addressed in Arabic studies, and this study is characterized by its closeness in time (1991-20003), and both the Turkish and Azeri republics have great importance and influence in the international arena. The research covers the origins of the common language between Turkey and Azerbaijan and how the Azeri Turkish language, which is one of the Branches of the Turkish language, as he explained the beginning of the relationship in the field of education, mentioning the most important agreements and protocols held between them, and official visits to both countries.Our research covers the following:1. The Turkish-Azeri language shared between the two countries.2. Scientific agreements and protocols between Turkey and Azerbaijan.Keywords: relations, Turkish language, Azerbaijan.